Application of allometry for determination of strength profile in young female athletes from different sports - Gajewski, J.; Busko, K.; Mazur, J.; Michalski, R. (Biology of Sport, 2011)
The goal of the study was to determine a strength profile in young female athletes practising different sports and to use allometry to evaluate muscular strength with respect to body mass. The study included 42 women who practised taekwondo (n = 10), weightlifting (n = 10), canoeing (n = 14) and speed skating (n = 8). Measurements of maximal muscle torques under static conditions in 10 groups of flexors and extensors of the elbow, shoulder, hip, knee and trunk were carried out. The MANCOVA procedure was employed to compare means between the groups. A logarithm of body mass was adopted as a covariate. Relationships between body mass and muscle torques in each muscle group were determined using a procedure of linear regression. The analysis of residuals was employed for the evaluation of maximal muscle torques. Mean values of logarithms of maximal muscle torques were significantly different for the representatives of individual sports and they depended on the logarithm of body mass. It was proposed to use a mean of residuals normalized for individual muscle groups as a synthetic strength index (mean of the strength profile). The women practising canoeing were characterized by the highest strength index. Its lowest values were obtained by weightlifting and taekwondo athletes. Differences in strength profiles in the tested athletes were attributed to the specific nature of their sports. It is suggested to use an allometric relationship scaled by body mass for strength assessment.